Influence of microstructure on rate-dependent response of unidirectional fibrous composites - Soňa Valentová; Michal Šejnoha; Jan Vorel; Zdeněk Prošek (Acta Polytechnica CTU Proceedings, 2022)
This paper outlines prediction of the macroscopic response of unidirectional fibrous composites made either from basalt or carbon fibers impregnated by a polymeric epoxy matrix. The viscoelastic response of the matrix phase was represented by the Maxwell chain model. A series of creep tests performed at several stress levels served as a stepping stone for the model calibration. The macroscopic behavior of both composites was first examined via computational homogenization. Attention was accorded to computational cells with variable size extracted from large representative images. We observed that selecting the computational model as a sufficiently large test window should be approached with caution. Because initial designs often need a large parametric study to test various material and geometrical patterns, this study was then supported by computationally much more effective Mori-Tanaka averaging scheme, clearly showing its potential even if loading the composite beyond its elastic limit.